Optimization of PV/T Solar Water Collector based on Fuzzy Logic Control - Ahmed, Omer K; Daoud, Raid W; Bawa, Shaimaa M; Ahmed, Ahmed H (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
Hybrid solar collector (PV/T) is designed to produce electricity, hot water, or hot air at the same time as they operate solar cells and solar heaters in one system. This system is designed to increase the electrical efficiency of solar cells by absorbing heat from these cells. The fuzzy logic (FL) is a tool usually used to optimize the operation of the systems. In this paper, the FL is to monitor and correct the mainsystem parameters to remain optimization efficiency at a better level. Three affected variables were studied: Effect of reflective mirrors, the effect of the glass cover, and the effect of the lower reflector angle on the performance of the PV / T hybrid solar system. These three parameters are traveled to be inputs for the FL, and the PV temperature in addition to system efficiency is the output for it. The effect of solar radiation was found to have a great effect on the efficiency of the hybrid solar collector. The thermal efficiency was 82% for the given value of the PV and mirrors, while the efficiency down to 50 for another angle. By using the artificial intelligent the system behavior depends on its output, which called feedback close loop control, at a real-time process that optimizes the system efficiency and its output.Â